Competency and Performance of Seaweed Farmers in Bantaeng Regency, South Sulawesi - Nuraeni Nuraeni; Andi Maslia Tenrisau Adam; Tsalis Kurniawan Husain; Fatimah Azzahra (Institut Pertanian Bogor, 2025)
Indonesia's marine area is around 70%, so seaweed is extensively cultivated in Indonesian waters. Although seaweed cultivation is thought to be simple, farmers confront numerous challenges. Poor farmer competence leads to low production quality, low product selling price, no negotiating position, inability to maintain production capacity, and lack of competitiveness. The purpose of this study was to assess seaweed farmers' production performance and competency. This study was undertaken in Bantaeng Regency, one of South Sulawesi Province's seaweed production centers. The Slovin algorithm was used to determine the number of respondents, which was 125 farmers. The method was Simple Random sampling. Descriptive analysis was used to describe seaweed farmers' performance and competence, whereas Kendall W Correlation analysis was used to determine the relationship between farmer attributes and seaweed farming competence. The results revealed an average dried seaweed yield of 3,390 kg per hectare. Seaweed farmers have a high level of technical competence in operating their farms, with a total score of 13,262, however managerial competence is poor, with a total score of 5,334. The association between farmer characteristics and agricultural competence demonstrates that age has a very strong relationship, as do education, farming experience, family dependents, and land area. To increase seaweed production and income, the government must develop an integrated extension program that improves farmers' technical and managerial skills. Keywords: farmer performance, managerial competence, seaweed, seaweed production, technical competence